Damous-el-Karita Die österreichisch-tunesischen Ausgrabungen der Jahre 1996 und 1997 im Saalbau und der Memoria des Pilgerheiligtumes Damous-el-Karita in Karthago - Dolenz, Heimo (Österreichisches Archäologisches Institut, 2001)
Two seasons of excavation (1996 and 1997) have been completed at the "subterranean rotunda" southeast of the Basilica Damous-el-Karita on the outskirts of ancient Carthage (Blg. 1/15, 16; Blg. 3; Abb. 1). 'Me purpose of the present study was re-evaluate the structures, construction period, finiction and wider significance of what was undoubtedly one of the most important Christian pilgrimage complexes in Norther Africa. The rectangular structure, which connected the basilica to the rotunda and has been seen as a porticus-fi-amed court turned out to be a three-aisled, basilica-Eke hall without an apse. The date of construction could be put at late fourth/early fifth century AD. Subsequently the structurre had been substantially rebuilt in two phases, firstly sometime between 530/565 AD and secondly at the end of the 6th to the beginning of the 7th century AD. A search of the literary sources allows one to tentatively suggest that the church-complex, known under its toponym "Damous-el-Kafita", could well be the celebrated basilica Fausti (Teil 1. 4). After the reconquista of Northerm Africa under the reign of emperor Justinian in 533 large hall (52 in by 30 in) was transformed. This transformation involved extensive rebuilding. To the north an atrium had been added. Whilst the eastern and western aisles were now Ranked by a rebuilt series of small rooms used as burial - cubicula (Blg. 1/14; Abb. 15). There is evidence for another renovation of the hall at the end of the 6th to the beginning of the 7th century by the construction of unsymmetrically situated ciborium foundations (BIg. 1/14), that refer to a one meter higher floor level. The rotunda was built no earlier than the second third of the 6th century, taking over the area of a pagan cemetery (Teil M. 3; Abb. 20), and is to be seen as an architectural mixtum compositurn (Teil M; BIg. 1, Blg. 3). As a Justinianic annex to the restored pilgrimage complex, the building typologically consists of a sigma (semicircular forecourt surrounded by a porticus; Tail 111. 4; Blg. 1/16), a martyriurn of the central type (groundfloor-ordtory possibly with an opaion; Teil Ill. 6; Abb. 86, Abb. 92) and a circular hall-crypt (sanctuary, Teil M. 5; Abb. 53, Abb. 59). Lateral, counterrotating staircases connect the different parts of the martyrium and are designed for massive pilgrimcirculation. 'Me centre of the crypt formed a ciborium of yellow Numidian marblestone, protecting the lost reliquary-shrine. The topography, metrological conception (reil Ill. 8; Abb. 96), architectural design and principle of pilgimage-circulation discussed above, suggests that this building was the spiritual center of the early Byzantine, orthodox pilgrimage complex of Damous-el-Karita. The design and the construction of the building suggest that the architect was from the Eastern pails of the empire, whilst the building force were native to Carthage. The nexus of a rotunda with a sigma, can typologicaly be traced back to 5th century AD palace-architecture in Constantinople. Elsewhere such a design is unknown. The realisation of a congruent plan of groundfloor and hall-crypt is until now unique in late antique architecture. As with the basilical hall, the groundfloor building of the martyrium was restyled and enlarged at the end of the 6th or at the beginning of 7th century AD by the creation of an ambulatory. The building seems to have fallen out of use some time around the end of that century. To sum up, the subterranean rotunda behind the basilica Damous-elKarita in Carthage was a two-perioded, early Byzantine martyriurn of the central type and the religious centre of the largest pilgrimage complex so far discovered in Carthage.